Methodological approach to modeling behavior changing and estimation of endurance industrial haggard objects - Grib Владимир Васильевич (Chrezvychaynye situatsii: obrazovanie i nauka, 2006)
This article discusses general methodological approach to modeling behavior changing and estimation of endurance mechanical systems during wear.